Aggression and Resentment in High–school students - Leal, Francisco; Meneses, Mónica; Alarcón, Andrés; Karmelic, Vesna (Revista de Psicología, 2005)
The relationship between aggressive behavior and resentment in vulnerable school contexts was studied, a relatively permanent emotional state that arises more probably in contexts of social discrimination or exclusion. Resentment was assessed with a specific scale and the severity of aggressive behavior was established from individual school records in 270 students attending grades 10 to 11 in a school within a context of high social vulnerability . The students with higher degrees of aggressive behavior also showed significantly more resentment than the other students. The suggestion is that aggressive behavior could be understood, at least in part, as reactive to the social violence present in these schools.